Pengembangan Lembar Kerja Peserta Didik Berbasis Project Based Learning pada Materi Keragaman Sosial dan Budaya Indonesia di Sekolah Dasar - Febriyani, Ananda; Hairida; Auliya Vilda Ghasya, Dyoty; Salimi, Asmayani; Pranata, Rio (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This study aimed to produce project-based learning Student Worksheets (LKPD) on social and cultural diversity material in Indonesia grade IV SDN 03 Pontianak Selatan which is suitable to be used to help the learning process in the independent curriculum. The study employed the Research and Development (R&D) method by adapting the ADDIE model. The subject of the study was a project-based learning LKPD on social and cultural diversity material in Indonesia, which was tested on 28 (twenty-eight) grade IV students and 2 grade IV teachers. Data collection techniques in this study are measurements and interviews—data measurement tools in the form of response questionnaires and interview guidelines. From the needs analysis, it was found that the LKPD used by teachers had not been designed by themselves; instead, they had been using available LKPDs. Teachers also complained when using these LKPDs because they did not explain the steps of the activities that students should do comprehensively. Additionally, teachers stated that materials containing various forms of social and cultural diversity in Indonesia are challenging to deliver due to the vast diversity spread throughout the Indonesian territory.  Before being tested, the product was validated by validators who then obtained a feasibility assessment of material expert validators on the content feasibility aspect of 91.25% with the "Very Valid" criteria, linguist validators on the linguistic feasibility aspect of 93% with the "Very Valid" criteria, and design experts on the graphic feasibility aspect of 95.71% with the "Very Valid" criteria. Furthermore, product trials through responses obtained "Very Decent" from teachers amounted to 95.83%. In comparison, responses from small group students amounted to 83.85% with the criteria "Very Good," and large group responses amounted to 86.75% with the criteria "Very Good". Thus, it is concluded that project-based learning student worksheets on social diversity and crocodile materials in Indonesia are very feasible to be used in the learning process.